FOREIGN INVESTMENT REGULATION IN THE SERVICES SECTOR IN AFRICA: SADC EXPERIENCE - Amos Saurombe (Obiter, 2017)
The growth of the service sector foreign direct investment (FDI) globally reflects an underlying need for appropriate regulation. As investors look into the African continent for investment opportunities, they need to find a regulated environment that can support their investments and related rights. This includes both intra-Africa FDI flows and investments that emanate out of the continent. The focus of this paper is on the Southern African Development Community (SADC). This paper will show that FDI will be critical for trade liberalization to be realised in the region. The findings of the paper point to the need for an institutional and regulatory framework in order to understand the consequences for investment flows. Where gaps are, appropriate cover needs to be found.